Postscript: Suggestions for Those Who Work and Play with Children, Youth and Adults - Beresin Anna; Bishop Julia; Beatty Chloé; Carter Caron; Egan Suzanne; LeBron Beatriz; Hazleton Ruth; Heljakka Katriina; Le Bigre Nicolas; Lewis Shanielia; McKinty Judy; Mitranić Nevena; et al. (Open book publishers, 2025)
The postscript presents the edited recorded transcript of two online conversations with the book’s contributing authors, with an additional written introduction by colleagues addressing the valuable play advocacy going forward. The document can be used as a springboard for training, policy development and future play research.
Play in a Covid Frame: Everyday Pandemic Creativity in a Time of Isolation